UPAYA MENULIS SURAT LAMARAN KERJA BAHASA INDONESIA MENGGUNAKAN MODEL THINK PAIRE SHARE - -, Kelara; Deliani, Susy; Lubis, Lailan Syafira Putri (Bahasa Indonesia Prima, 2023)
This research is a descriptive qualitative research. Data collection was done using observation, essay tests, and documentation methods. This study analyzes student errors based on test results on students' ability to write job application letters. Errors in writing job application letters often occur in the writing stages, such as content, word choice, sentences, paragraphs, and spelling on job application letters. Researchers used the think pair share model. This type of learning model is very suitable for students and helps researchers carry out learning activities in writing application letters. The subjects of this study were students of class XII TBSM and XII TKJ, totaling 60 people. In this study, students were given an essay test in writing a job application letter in the form of a description, then analyzed for errors based on the Indonesian correspondence guide with different types of errors for each category of errors. Obtained from the conclusion, the problem that arises from the background of the problem is in what way the efforts of class XII students of SMK PAB 1 Helvetia in writing essential parts using spelling on job application letters. The results of the data analysis show the control class with an average score of 66 and the experimental results with an average score of 81. Students using the think pair share model are more active in learning, asking questions, and answering questions posed by researchers using the think pair share model.